2013
DOI: 10.1136/bcr-2012-008238
|View full text |Cite
|
Sign up to set email alerts
|

Chronic eosinophilic pneumonia with persistent decreased diffusing capacity for carbon monoxide

Abstract: SUMMARYWe report a 15-year-old girl presenting with dry cough, exertional dyspnoea, weight loss, fever and night sweats for over 1 month. Blood tests revealed hypereosinophilia, high IgE and antinuclear antibodies levels. Chest x-rays showed bilateral peripheral infiltrates mostly in the right upper lobe which was confirmed by a chest CT. Bronchoalveolar lavage showed hypercellularity with 28% of eosinophils. Idiopathic chronic eosinophilic pneumonia was confirmed after exclusion of other causes of eosinophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Recent studies have revealed that reduced lung CO diffusing capacity is a significant predictor of subclinical disease activity and recurrence in patients with CEP. 11 The lesions on pulmonary imaging of the 20 cases were bilateral, non-migratory with clear boundaries, and they were mainly distributed in the periphery or subpleura. The most common lesions were patchy shadows, followed by consolidation and ground glass shadows.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent studies have revealed that reduced lung CO diffusing capacity is a significant predictor of subclinical disease activity and recurrence in patients with CEP. 11 The lesions on pulmonary imaging of the 20 cases were bilateral, non-migratory with clear boundaries, and they were mainly distributed in the periphery or subpleura. The most common lesions were patchy shadows, followed by consolidation and ground glass shadows.…”
Section: Discussionmentioning
confidence: 93%
“…After treatment, pulmonary function improved rapidly. Recent studies have revealed that reduced lung CO diffusing capacity is a significant predictor of subclinical disease activity and recurrence in patients with CEP 11 …”
Section: Discussionmentioning
confidence: 99%
“…After treatment, pulmonary function improved rapidly. Recent studies have revealed that reduced lung CO diffusivity is a signi cant predictor of disease subclinical activity and recurrence in CEP patients [11].…”
Section: Discussionmentioning
confidence: 99%